PENGARUH KOMPETENSI DAN PENEMPATAN TERHADAP SEMANGAT KERJA DAN KINERJA PEGAWAI DINAS PENDAPATAN DAERAH KABUPATEN BENGKALIS - Saputra, Billy Yanis; Hendriani, Susi; Machasin, Machasin (Jurnal Tepak Manajemen Bisnis, 2017)
This study aimed to determine the effect of competence and placement to spirit at work and performance of employees at Department of Revenue District Bengkalis. This study uses primary data is the data obtained from the interviews and giving questionnaires to all employees UPTD at Department of Revenue District Bengkalis. Secondary data were obtained relating to the object and the organizational structure. The analytical method used in this study is path analysis with SPSS. From the results of the testing that has been done, there is a direct influence of competence on the performance for 0,530, the indirect effect between competence on performance through spirit at work of 0.582, the direct effect of the placement on the performance of 0,243, the indirect effect between competence on performance through spirit at work of 0.321, and spirit at work influence on the performance of 0.192. Results of calculation of the coefficient of determination (R2) is approximately 4.73, which means, variable competence, placement and spirit at work to performance of employees by 73.4%, while the remaining 26.6% is influenced by other variables not included in this study model.